Raised intracranial pressure. Issue 6 (June 2017) - Rajesh, Ambika; Kingston-hepner, Miranda; Krishnakumar, Deepa
Abstract: Raised intracranial pressure (ICP) is a medical and potential neurosurgical emergency. Prompt recognition and appropriate intervention prevents morbidity and mortality due to the underlying cause. Raised ICP has a wide variety of aetiologies. The main aim in the management of these patients is to prevent secondary injury to the brain. The approach to these patients follows the principles of initial stabilisation and specific management to address raised ICP. Basic understanding of physiology of intracranial pressure helps in determining appropriate diagnostics and correct interventions. This review discusses the known physiology and offers advice for clinicians caring for children with raised intracranial pressure. We describe the currently available methods of measurement and their limitations. We give advice on clinical detection, diagnosis and management of acute and chronically raised ICP in children.